Estonian book historiography - Lott, Mare (Knygotyra, 1988)
he scientific study of the history of the Estonian book began in the 1930s, and some essays published then have not lost their value up to the present. During this period, the fundamentals of book statistics and the first comprehensive history of the Estonian book by F. Puksoo were published. The attention of researchers was mainly concentrated on 16th-17th, and partly 18th-century publications. During the post-war period, there was no leading center for book study, and the research concentrated at the major libraries. The problems of book history and research were also studied in the Department of Bibliography, first at Tartu University and then at Tallinn Pedagogical Institute. In the 1960s, Estonian post-war book historiography achieved more serious results. Republican scientific conferences on book study became a significant factor in the development of book science. The opportunities for publishing improved significantly. The entire potential was used for the collective monograph about the history of the Estonian book, which commemorated the 450th anniversary of Estonian printed books in 1975. In the 1980s, researchers’ attention was concentrated on the development of printing. During more than 50 years of study of books and book problems, a large body of factual material has been assembled and generalized. However, the development of the theoretical basis of the study of the Estonian book and the publication of research results is hindered by the lack of a center for scientific book study.